EFEKTIVITAS METODE KOLABORATIF DALAM PEMBELAJARAN MENULIS - Sri Hapsari Wijayanti (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
This study aims to describe how the subjects of this study have done the editing steps and to figure out whether collaborative writing method as one of the process in academic writing, i.e. editing steps, can be used by lecturers to teach bahasa Indonesia in college. Different from previous studies, this study is focused on men and women’s choices towards the use of collaborative writing. Based on the data from sixty subjects at Economic Faculty of Atma Jaya Catholic University Jakarta, using quasi-experimental design, the researcher gathered the data through test essay writing, questionnaires, and in-depth interview. This study found out that collaborative writing is  interesting,  useful,  and  not  boring.  Male  students  like  this  method  more  than women.